The Effectiveness of HOTS (Higher Order Thinking Skill) in Teaching Reading Comprehension - Afida Munawati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
This objective of this research is to find out whether or not Higher Order Thinking Skill (HOTS) is effectives in teaching reading comprehension. Related to the educational issue in the International level, Indonesian government creates a higher education system. Indonesian student must be able to think creatively and critically to compete in the global competitions in 21 century. Several studies investigate in a different ways in practices higher order thinking skill used by the teacher. The teacher integrates of this skill into curriculum and the application methods. This research uses short answer questions test to know the effect of higher order thinking skill. This research took place at an Islamic junior high school Darul Huda in Blitar. Randomly sampling where used in this research and 50 participants were included. The research instrument test which divided into pre-test and post-test, and then statistical differences were tested based on the score of post-test on both group in term of significant.